Building sustainable and resilient surgical systems: A narrative review of opportunities to integrate climate change into national surgical planning in the Western Pacific region - Rennie X. Qin; Lotta Velin; Elizabeth F. Yates; Omnia El Omrani; Elizabeth McLeod; Jemesa Tudravu; Lubna Samad; Alistair Woodward; Craig D. McClain (Elsevier, 2022)
Summary: Five billion people lack access to surgical care worldwide; climate change is the biggest threat to human health in the 21st century. This review studies how climate change could be integrated into national surgical planning in the Western Pacific region. We searched databases (PubMed, Web of Science, and Global Health) for articles on climate change and surgical care. Findings were categorised using the modified World Health Organisation Health System Building Blocks Framework. 220 out of 2577 records were included. Infrastructure: Operating theatres are highly resource-intensive. Their carbon footprint could be reduced by maximising equipment longevity, improving energy efficiency, and renewable energy use. Service delivery Tele-medicine, outreaches, and avoiding desflurane could reduce emissions. Robust surgical systems are required to adapt to the increasing burden of surgically treated diseases, such as injuries from natural disasters. Finance: Climate change adaptation funds could be mobilised for surgical system strengthening. Information systems: Sustainability should be a key performance indicator for surgical systems. Workforce: Surgical providers could change clinical, institutional, and societal practices. Governance: Planning in surgical care and climate change should be aligned. Climate change mitigation is essential in the regional surgical care scale-up; surgical system strengthening is also necessary for adaptation to climate change.